ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ISPA PADA SANTRI DI PONDOK PESANTREN MA'HAD IBNUL MUBAROK KOTA SAMARINDA TAHUN 2025 - Yusfa Iswinda Itaqullah; Suhat; Agus Riyanto; Dyan Kunthi Nugraheni; Novie Elvinawaty Mauliku (Jurnal Riset Kesehatan, 2026)
Acute Respiratory Infection (ARI) represented a prevalent health issue in Islamic boarding school (pesantren) environments due to communal living systems and high activity density. This study aimed to analyze host and environmental factors associated with the ARI incidence among students (santri) at the Ma'had Ibnul Mubarok Islamic Boarding School in Samarinda City in 2025. This quantitative research employed an observational analytic approach with a case-control design. The research sample consisted of 110 santri selected through a purposive sampling technique. Data collection was conducted using structured questionnaires, anthropometric measurements, and direct environmental observations. Bivariate analysis using the chi-square test showed significant associations between age (), comorbidity (), room ventilation (), and environmental cleanliness () with ARI incidence. Multivariate analysis via multiple logistic regression revealed that room ventilation was the most dominant factor with an Odds Ratio of 103.737 (95% CI: 7.851–1370.656). This wide confidence interval reflected a very strong environmental effect observed within a relatively small sample size. Boarding school management was recommended to improve room ventilation systems and enhance environmental cleanliness to strategically reduce ARI incidence.